Indicators and correlates of low energy availability in male and female dancers. Issue 1 (26th November 2020) - Keay, Nicola; Overseas, AusDancers; Francis, Gavin
Abstract : Objectives: To investigate indicators and correlates of low energy availability (LEA) in male and female dancers. Methods: A Dance-Specific Energy Availability Questionnaire (DEAQ) was developed and administered online internationally to dancers training at preprofessional, professional or advanced amateur level. The DEAQ drew on current validated, published questionnaires for LEA, linked to the clinical outcomes of relative energy deficiency in sport (RED-S). Questions addressed recognised physiological indicators and consequences of LEA in the context of dance, together with potential correlates. LEA was quantified using a scoring system to include these characteristics. Results: 247 responses to the DEAQ were analysed (225 female and 22 male), mean age 20.7 years (SD 7.9) with 85% practising ballet. Psychological, physiological and physical characteristics consistent with LEA were reported by 57% of the female dancers and 29% of male dancers, indicating a risk of RED-S. The unique nature of dance training, in terms of demands and environment, was found to be potentially influential in development of this situation. Less than one-third (29%) of dancers were aware of RED-S. Conclusion: This study found dancers to be a specific group of high-level artistic performers displaying indicators of LEA and consequently at risk of developing the adverse clinical health and performance consequences of RED-S. Awareness of RED-S was low. The DEAQ has the potential to raise awareness and be a practical, objective screening tool to identify dancers in LEA, at risk of developing RED-S.